Simulation Battery Cooling System for Small Scale Electric Vehicle (Light EV) (Journal of Transport System Engineering, 2022)
The Battery Thermal Management System (BTMS) has widely used for Electric Vehicle (EV) as cooling system to reduce high temperature occurred from batteries source during discharge and charge process. Since the performance and cycle life of batteries are very sensitive to temperature, it important to maintain the proper temperature range in order to avoid the thermal issues and improve the performance. Therefore, the purpose of this project is to study the effectiveness of different type of cooling system for small scale Electric Vehicle (EV). The study is conducted by using two main types of cooling system that available in electricity grid which is air cooling and liquid cooling. In order to evaluate the effectiveness of those cooling system, an analysis is conducted by developing an EV model using MATLAB/Simulink software and simulated at different speed of the vehicle from the few driving cycle that commonly used in researcher paper. Based on the analysis, the maximum temperature of battery for liquid cooling system under NEDC, WLTP, and HWFET is 23.14 ⁰C, 23.3 ⁰C and 23.09 ⁰C compare to air cooling system which is 24.66 ⁰C, 26.3 ⁰C and 24.4 ⁰C respectively at 23 ⁰C of ambient temperature. As the result of this project is showed that the liquid cooling system are more effective to maintain the temperature of battery as the temperature rise more controlled compare to air cooling.
Keywords: Battery Thermal Management System (BTMS), liquid cooling, air cooling, MATLAB/Simulink, Electric Vehicle.